Knowledge, Attitude and Practice of Syrian Mothers' Towards Diarrhea Management and Prevention Among Under-Five Children: A Cross Sectional Study from Syria - Haidara Bohsas; Sarya Swed; Hidar Alibrahim; Bisher Sawaf; Mohamed Elsayed (University Library System, University of Pittsburgh, 2022)
Background: Diarrhea kills more than 2,000 children worldwide and over 1.3 million annually. There is still a gap in home management knowledge, attitude, and excellent practice of diarrheal illness.This research aims to understand mothers' knowledge, attitudes, and behaviours about diarrhoea in children under the age of five in Syria to minimize the number of fatalities and enhance the efficacy and efficiency of treatment.    Methods: From the 8th to the 18th of September 2022, a cross-sectional online survey was done in Syria. The questionnaire was modified based on prior research that used a thorough, validated scale. Mothers having at least one child under the age of five and Syrian nationalities from all Syrian governorates were eligible to participate in the study. Four components make up the questionnaire. In the first section, information regarding the participants' demographics was provided. In the second section, mothers were tested on their knowledge of diarrhoea. Mothers' actual attitudes regarding preventing and treating diarrhoea were also analyzed.   Results: 49.9% of the 996 participants were between the ages of 25 and 34, while 62.6% of the children were between the ages of 26 and 59 months. 46.2 percent of participants had a Bachelor's degree. 82.4 % of moms classified diarrhoea as the frequent passage of watery stools (3 or more times). 53.7 percent of respondents had used ORS; however, only 33.7% said they knew how to prepare it. Mothers with children aged 25-59 months were more informed about the prevention and home-based treatment of diarrhoea in their children (mean=6.07, SD= 2.36) than those aged 35-44 (mean=6.16, SD= 2.36). Mothers' excellent economic status was associated with greater diarrhoea management knowledge (mean=6.5, standard deviation = 2.50). (Mean = 7.28, Standard Deviation = 2.50) Mothers with a high school diploma or above had more understanding of diarrhoea management than those with a lower level of education. 28.7% of mothers with children between 25 and 59 months exhibited excellent knowledge of prevention and home-based treatment of diarrhoea. 43.4% of mothers with a bachelor's degree or more showed a positive attitude toward diarrhoea management. Only 6.3% of moms with a low socioeconomic position have shown appropriate diarrhoea control practices. Three out of six predictor factors were substantially connected with mothers' attitudes about diarrhoea management, including the age of the child, the mother's employment, and her level of education (P0.05). Two of the six predictor factors were substantially connected with mothers' practice of diarrhoea control, including the mother's employment and socioeconomic position (P0.05). Women with higher socioeconomic status are expected to perform diarrhoea treatment 1.69 times more often than those with a lower socioeconomic status.   Conclusion: We indicated that mothers' beliefs and actions about the prevention and home management of diarrheal illnesses in children younger than five were inadequate. Therefore, it is important to plan and execute health education, information distribution, and community discourse to improve the prevention and treatment of diarrhea in children under five.